Fe3O4-SiO2-Alginate Photocatalyst for Textile Dyes Waste Degradation - Sri Wardhani; Herdian Akbar Mardiansyah; Danar Purwonugroho (Science and Technology Indonesia, 2023)
Fe3O4 is a photocatalyst that is used to degrade textile dye waste which can be collected and reused. Fe3O4 was prepared by coprecipitation method, then impregnated with SiO2 and sodium alginate. The purposes of this study were to investigate the degradation of textile dye waste using a Fe3O4-SiO2-alginate photocatalyst, to examine the light and dark test of photocatalyst under the influence of concentration and irradiation time. The type of light used was a 14.5-watt Philips LED lamp with a wavelength of 400-640 nm. Photocatalyst characterizations were conducted using FTIR, UV-Vis DRS, and XRD. The light and dark test of photocatalyst was carried out by photodegradation of textile dye waste with 0.5 g of photocatalyst with concentrations of 5%, 10%, and 15% and irradiation times were varied for 60, 90, 120 min. The degradation results were measured by calculating the COD value. The results of characterization by FTIR showed that the photocatalyst Fe3O4-SiO2-Alginate had absorption at wavelengths of 637.56 cm−1 and 3365.86 cm−1 which indicated the Fe-O-Si functional group and O-H stretching vibration. Results of UV-Vis DRS were analyzed using Origin Pro 2022 and revealed that the band energy gap for Fe3O4 and Fe3O4-SiO2 were 2.20 eV and 1.77 eV, respectively. The XRD results analysis with Match!3 software showed that for Fe3O4 had magnetite phases, while SiO2 had amorphous cristobalite phases. The 15% (w/v) Fe3O4 concentration in the form of powder and granules degraded batik liquid waste by 79.6% and 84.48%, respectively.